Assessing alcohol industry penetration and government safeguards: the International Alcohol Control Study - Sarah Callinan; Gopalkrishna Gururaj; Shiwei Liu; Sally Casswell; Thomas Karlsson; Jintana Jankhotkaew; Surasak Chaiyasong; Pranil Man Singh Pradhan; Gillian Shorter; Timothy Naimi; Ingeborg Rossow; Keitseope Nthomang; et al. (BMJ Global Health)
Background The alcohol industry uses many of the tobacco industry’s strategies to influence policy-making, yet unlike the Framework Convention on Tobacco Control, there is no intergovernmental guidance on protecting policies from alcohol industry influence. Systematic assessment of alcohol industry penetration and government safeguards is also lacking. Here, we aimed to identify the nature and extent of industry penetration in a cross-section of jurisdictions. Using these data, we suggested ways to protect alcohol policies and policy-makers from undue industry influence.Methods As part of the International Alcohol Control Study, researchers from 24 jurisdictions documented whether 22 indicators of alcohol industry penetration and government safeguards were present or absent in their location. Several sources of publicly available information were used, such as government or alcohol industry reports, websites, media releases, news articles and research articles. We summarised the responses quantitatively by indicator and jurisdiction. We also extracted examples provided of industry penetration and government safeguards.Results There were high levels of alcohol industry penetration overall. Notably, all jurisdictions reported the presence of transnational alcohol corporations, and most (63%) reported government officials or politicians having held industry roles. There were multiple examples of government partnerships or agreements with the alcohol industry as corporate social responsibility activities, and government incentives for the industry in the early COVID-19 pandemic. In contrast, government safeguards against alcohol industry influence were limited, with only the Philippines reporting a policy to restrict government interactions with the alcohol industry. It was challenging to obtain publicly available information on multiple indicators of alcohol industry penetration.Conclusion Governments need to put in place stronger measures to protect policies from alcohol industry influence, including restricting interactions and partnerships with the alcohol industry, limiting political contributions and enhancing transparency. Data collection can be improved by measuring these government safeguards in future studies.